2002
DOI: 10.1111/j.1751-0813.2002.tb12474.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent spirochaetal infections of the feet and colon of cattle in Japan

Abstract: Concurrent infections with morphologically similar spirochaetal organisms may occur in the feet and colon of cattle in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
(41 reference statements)
1
16
0
1
Order By: Relevance
“…In Japan, PDD in dairy cattle is now found in most regions (24,26,37) since the first case was reported in 1992 (20). PDD begins as a superficial dermatitis with an erosive lesion and later forms a hyperkeratotic papillomatous lesion with long hairlike projections (12).…”
mentioning
confidence: 99%
“…In Japan, PDD in dairy cattle is now found in most regions (24,26,37) since the first case was reported in 1992 (20). PDD begins as a superficial dermatitis with an erosive lesion and later forms a hyperkeratotic papillomatous lesion with long hairlike projections (12).…”
mentioning
confidence: 99%
“…Intestinal spirochetes in cattle and deer have been reported to be pathogenic [5][6][7], whereas those in the horse are considered to be part of the normal intestinal flora and to be nonpathogenic [1,2]. Since invasive intestinal spirochetes were demonstrated in the intestinal lesions of the present animal by immunohistochemical and ultrastructural methods, they were thought to have played an important role in the pathogenesis of colitis and diarrhea.…”
mentioning
confidence: 80%
“…However, despite extensive research, a specific infectious agent has not been identified, and it has been suggested that the disease may be a polymicrobial infection (Döpfer et al, 1997). The range of bacteria cultured from DD lesions includes Campylobacter sputorum (Shibahara et al, 2002), Porphyromonas levii, Fusobacterium necrophorum, Fusobacterium nucleatum, Prevotella oralis, Prevotella denticola, Prevotella bivia, Treponema brennaborense (Schrank et al, 1999) and as-yet unnamed treponemes (Demirkan et al, 1999;Stamm et al, 2002;Walker et al, 1995). By using culture-independent methods, such as immunocytochemistry and 16S rRNA gene sequence analysis, additional organisms were detected in lesions and were related to Bacteroides levii, Borrelia burgdorferi, Mycoplasma hyopharyngis and several Treponema species (Collighan & Woodward, 1997; Demirkan et al, 1998; Moter et al, 1998).…”
Section: Tierarztpraxis Ch-3186 Dü Dingen Switzerlandmentioning
confidence: 99%
“…Dermatitis digitalis (DD), also known as Mortellaro disease or strawberry foot, is an economically important ulcerative disease affecting the bovine foot in an increasing number of countries including Germany, Italy, Japan, the Netherlands, Switzerland, the UK and the USA and may be the dominant cause of lameness in dairy cows (Blowey & Sharp, 1988;Choi et al, 1997;Collighan & Woodward, 1997;Collighan et al, 2000;Demirkan et al, 1998;Luginbühl & Kollbrunner, 2000;Moter et al, 1998;Schrank et al, 1999;Shibahara et al, 2002;Walker et al, 1995). The reported spread between herds by veterinarians, foot trimmers and purchased animals as well as curing of the condition by antibiotic therapy are characteristics of an infectious disease (Laven, 2001).…”
mentioning
confidence: 99%